Structure and properties of Al-Ni PM composites - Nath D.; Tiwari S.N.; Babu S.K. (My University, 2025)
Al-Ni powder mixtures containing 2, 4, 6 and 8 wt-% nickel were compacted at 125, 250, 375 and 500 MPa and sintered at 620, 630 and 640°C in a nitrogen atmosphere. The sintered density, sintered hardness and strength of composites thus produced were determined as a function of compaction pressure and sintering temperature. Wear rates of the composites were evaluated as a function of applied load and sliding velocity. Optical and scanning electron microscopy were used to reveal the morphology of powder and microstructures of green and sintered compacts. X-ray diffraction studies of the sintered compacts were made to confirm the phases formed on sintering. Sintered density, sintered hardness and strength increased with an increase in compaction pressure and nickel content. X-ray diffraction indicated the presence of Al 3Ni phase in the sintered alloy. The wear rate of the sintered Al-Ni PM composite was found to increase with increasing load and decrease with increasing nickel content. © 2004 Institute of Materials, Minerals and Mining.